Microstructure control in the growth of large area T1-2212 thin films - Wu, H; Speller, S; Pal, S; Edwards, D; Grovenor, C (2003)
Large area high temperature superconducting thin films are needed for the implementation of a range of passive microwave devices. We have been investigating the critical processing issues that control the surface resistance values in 2 inch films grown on lanthanum aluminate substrates, including the possibility of batch processing wafers in a vertical geometry. We have shown that the microstructure of vertically-processed films shows a systematic variation in microstructure from top to bottom which can seriously degrade the uniformity of the superconducting properties. We have also used electron backscattered diffraction to analyze the fine-scale mosaic structure of thin films of varying thickness and processing conditions to show that the best surface resistance values are not found in films with the sharpest epitaxial relationship between the substrate and film. We propose an explanation for this counterintuitive observation based on how the films can relieve stresses generated during processing.